Le père et sa fille : le sceau paternel dans la prose colettienne et beauvoirienne - Ledwina, Anna (Romanica Silesiana)
The character of the father in French literature, especially in the works of Sidonie-Gabrielle Colette and Simone de Beauvoir, is significant. He may be perfect or not without faults, withdrawn or authoritative, fascinating or disgusting, but invariably – even if he is overshadowed by the mother – the father inspires his daughter. The latter treats him as a kind of spiritual guide, a confidant who gives her life energy, is an example to follow, and passes on his value system and the need to write on his daughter. Love for the father or the lack thereof allows an adolescent daughter to find her own identity and define herself, and in the case of a mature woman it allows her to revisit her own childhood and youth through writing, so as to resurrect the image of the father and reflect on her own life and the writer’s vocation.